Perbedaan Jumlah Koloni Bakteri Pada Tangan Sebelum dan Sesudah Cuci Tangan Menggunakan Sabun - Faradila Nur Aulia; Norma Farizah Fahmi (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2022)
Hands are vectors of disease-causing bacteria that can cause migration from one person to another or direct or indirect contact. The bacteria on our hands can be removed if we wash our hands with soap. The purpose of this study was to analyze the difference in the number of bacterial colonies on the hands before and after washing them with soap on the Student.Health.Analyst.of.STIKes Ngudia.Husada.Madura. The research method used is quantitative, and the research design used a pretest-posttest with a control group. The variable of this research was the number of bacterial colonies contained in the media using the pour plate method. The sample used is 16 samples with a total populasi of 53 respondents. This research was conducted at the Microbiology Laboratory of STIkes Ngudia Husada Madura. The results obtained from this study indicate that there was a significant difference in the decrease in the number of bacterial colonies on hands before and after washing hands with soap, with the results of data analysis using Wilcoxon showing a significance value of 0.000. Therefore, washing hands with soap can reduce the number of bacteria found on the hands, with an average colony at the time of before washing hands as much as 201,9375 x 104 colonies/ml while after wasing hands is 93.0625 x104 colonies/ml.